2020
DOI: 10.3390/tropicalmed5020052
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Role of the Diagnostic ‘Reflex’ in the Elimination of Human African Trypanosomiasis

Abstract: To successfully eliminate human African trypanosomiasis (HAT), healthcare workers (HCWs) must maintain their diagnostic acuity to identify cases as the disease becomes rarer. HAT experts refer to this concept as a ‘reflex’ which incorporates the idea that diagnostic expertise, particularly skills involved in recognising which patients should be tested, comes from embodied knowledge, accrued through practice. We investigated diagnostic pathways in the detection of 32 symptomatic HAT patients in South Sudan and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…In the case of human African trypanosomiasis (HAT), anthropologists found that a diagnostic reflex among healthcare workers is stronger when they are in the habit of testing and have time and space to consider symptoms and that this reflex also exists among communities and patients. A diagnostic reflex can be trained in times of elimination by treating detection of events as important learning opportunities and ensuring multidimensional access to diagnostics across the health system [ 40 ]. These data show that in order to make new technologies such as the biosensor accessible, malaria needs to be made and kept visible.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of human African trypanosomiasis (HAT), anthropologists found that a diagnostic reflex among healthcare workers is stronger when they are in the habit of testing and have time and space to consider symptoms and that this reflex also exists among communities and patients. A diagnostic reflex can be trained in times of elimination by treating detection of events as important learning opportunities and ensuring multidimensional access to diagnostics across the health system [ 40 ]. These data show that in order to make new technologies such as the biosensor accessible, malaria needs to be made and kept visible.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of human African trypanosomiasis (HAT), anthropologists found that a diagnostic re ex among healthcare workers is stronger when they are in the habit of testing and have time and space to consider symptoms and that this re ex also exists among communities and patients. A diagnostic re ex can be trained in times of elimination by treating detection of events as important learning opportunities and ensuring multidimensional access to diagnostics (28). These data show that in order to make new technologies such as the biosensor accessible, malaria needs to be made and kept visible.…”
Section: Discussionmentioning
confidence: 99%
“…While following the script was emphasised by all testers as the most important way to avoid misdiagnoses, our observations showed that testers also frequently used embodied knowledgeor at least their syndromic familiarity with HIV (Palmer et al, 2020) to evaluate the likelihood that a test result was trustworthy. Testers were aware that this practice went against the principles they had learned in their training, where the need for an unbiased, 'open mind' was emphasised.…”
Section: Embodied Knowledgementioning
confidence: 86%